2014
DOI: 10.1128/aem.01845-14
|View full text |Cite
|
Sign up to set email alerts
|

Haloalkylphosphorus Hydrolases Purified from Sphingomonas sp. Strain TDK1 and Sphingobium sp. Strain TCM1

Abstract: Phosphotriesterases catalyze the first step of organophosphorus triester degradation. The bacterial phosphotriesterases purified and characterized to date hydrolyze mainly aryl dialkyl phosphates, such as parathion, paraoxon, and chlorpyrifos. In this study, we purified and cloned two novel phosphotriesterases from Sphingomonas sp. strain TDK1 and Sphingobium sp. strain TCM1 that hydrolyze tri(haloalkyl)phosphates, and we named these enzymes haloalkylphosphorus hydrolases (TDK-HAD and TCM-HAD, respectively). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…These strains are considered to sequentially hydrolyze the three phosphoester bonds of TDCPP and TCEP using three kinds of phosphoesterases: phosphotriesterase (PTE), phosphodiesterase (PDE), and phosphomonoesterase (PME). We identified PTEs capable of degrading TDCPP and TCEP in both strains and named them haloalkylphosphorus hydrolase (HAD) ( 4 ). However, PDEs and PMEs involved in the degradation have not yet been identified.…”
Section: Genome Announcementmentioning
confidence: 99%
“…These strains are considered to sequentially hydrolyze the three phosphoester bonds of TDCPP and TCEP using three kinds of phosphoesterases: phosphotriesterase (PTE), phosphodiesterase (PDE), and phosphomonoesterase (PME). We identified PTEs capable of degrading TDCPP and TCEP in both strains and named them haloalkylphosphorus hydrolase (HAD) ( 4 ). However, PDEs and PMEs involved in the degradation have not yet been identified.…”
Section: Genome Announcementmentioning
confidence: 99%
“…The OPs used in our MIX treatment are proven to be degradable and hence can be used as a resource for bacteria (Leahy and Colwell, ; Takahashi et al ., , , , ; Seo et al ., ; Abe et al ., , ; Joye et al ., ; Kera et al ., ; Vila‐Costa et al ., )). Yet, our study showed notably negative effects on bacterial growth of hydrocarbons and OPEs supplied at environmentally relevant concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…strain TCM1 (i.e. Sb-PTE) is of interest [102]. These enzymes are particularly reactive toward a group of OP triesters that are frequently used as plasticizers, durable plastics, foams and flame retardants.…”
Section: Op Hydrolases (Ophs)mentioning
confidence: 99%